ANALISIS EXERGY PADA UNIT 2 PEMBANGKIT LISTRIK TENAGA GAS (PLTG) TELUK LEMBU KAPASITAS 21.6 MW - Awaludin Martin; Nur Indah Rivai (Jurnal Sains dan Teknologi, 2019)
Many efforts have been made in energy efficiency in electricity generation. One way to improve the efficiency of energyuse is by conducting an analysis. Analysis meant here is the exergy analysis and exergoeconomic analysis. The conceptof this analysis, not only the quantity of energy but also the quality of energy (the second law of thermodynamics). Exergyis done by sampling Teluk Lembu gas turbine power plant capacity 21.6 MW. The aim of this study was to analyze theexergy destruction and the amount of the exergy destruction in the form of cost. The result showed that the highest exergydestruction occurred in the combustion chamber reached 21,85 MW and while gas turbine is the lowest 3,09 MW andefficiency exergetic was 22,73%. Based on the calculation, analysis of exergy can determine magnitude, location of theexergy destruction. These will make it easier to conduct optimizations to increase efficiency